Heidi - Spyri, Johanna (Oxford University Press Oxford, 2015)
When Heidi is sent to live in the Swiss mountains with her bad-tempered old Grandfather, everyone in the village feels sorry for her. What will a little girl do in such an isolated home, and with such a grumpy companion?